2024
DOI: 10.1002/ece3.11103
|View full text |Cite
|
Sign up to set email alerts
|

Population genomic evidence of structured and connected Plasmodium vivax populations under host selection in Latin America

Johanna Helena Kattenberg,
Pieter Monsieurs,
Julie De Meyer
et al.

Abstract: Pathogen genomic epidemiology has the potential to provide a deep understanding of population dynamics, facilitating strategic planning of interventions, monitoring their impact, and enabling timely responses, and thereby supporting control and elimination efforts of parasitic tropical diseases. Plasmodium vivax, responsible for most malaria cases outside Africa, shows high genetic diversity at the population level, driven by factors like sub‐patent infections, a hidden reservoir of hypnozoites, and early tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 130 publications
6
9
0
Order By: Relevance
“…The geographic distribution of genetic diversity across the Latin American region revealed that P. vivax populations along the Pacific coast (Colombia and Peru) exhibited lower genetic diversity (π) compared with Amazonian populations (Brazil, French Guiana, and Venezuela) (S9 Fig.). This is in line with previous studies [36,54], and could stem from transmission pattern variations across regions [36]. Indeed, coastal areas experience more periodic malaria transmission events compared with the Amazon region, where transmission is more stable throughout the year [55,56].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The geographic distribution of genetic diversity across the Latin American region revealed that P. vivax populations along the Pacific coast (Colombia and Peru) exhibited lower genetic diversity (π) compared with Amazonian populations (Brazil, French Guiana, and Venezuela) (S9 Fig.). This is in line with previous studies [36,54], and could stem from transmission pattern variations across regions [36]. Indeed, coastal areas experience more periodic malaria transmission events compared with the Amazon region, where transmission is more stable throughout the year [55,56].…”
Section: Discussionsupporting
confidence: 90%
“…2c). Specially, two distinct genetic clusters were identified, as previously observed [13,29,36]: (1) isolates from Mexico, Honduras, and Colombia gathered together as a Central American group, and (2) isolates from the French Guiana, Guyana, and Venezuela formed another distinct cluster as an Amazonian group (Fig. 2d).…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations